2008
DOI: 10.1098/rsif.2007.1336
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of a microfibril subjected to shear and normal loads

Abstract: Many synthetic bio-inspired adhesives consist of an array of microfibrils attached to an elastic backing layer, resulting in a tough and compliant structure. The surface region is usually subjected to large and nonlinear deformations during contact with an indenter, leading to a strongly nonlinear response. In order to understand the compliance of the fibrillar regions, we examine the nonlinear deformation of a single fibril subjected to a combination of shear and normal loads. An exact closed-form solution is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…The force was measured using weight balances, [67,74] surface-probe [43,49] or microsphereterminated, [38,48,51,57,66,77,88,[92][93][94] nanoindenters, [86,87,95] or forceload cells coupled to monitorized stages [50,80,96] ). In some cases the adhesion setup is combined with a high-magnification video microscope to image the real contact area during the experiment [31,46,47,[97][98][99][100] or the lateral deformation profile of the fibrils during loading or retraction. [51] Measurements using spherical and flat indenters were reported.…”
Section: Testing Methodsmentioning
confidence: 99%
“…The force was measured using weight balances, [67,74] surface-probe [43,49] or microsphereterminated, [38,48,51,57,66,77,88,[92][93][94] nanoindenters, [86,87,95] or forceload cells coupled to monitorized stages [50,80,96] ). In some cases the adhesion setup is combined with a high-magnification video microscope to image the real contact area during the experiment [31,46,47,[97][98][99][100] or the lateral deformation profile of the fibrils during loading or retraction. [51] Measurements using spherical and flat indenters were reported.…”
Section: Testing Methodsmentioning
confidence: 99%
“…5a). [5][6][7]9,11,14,21,[31][32][33][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] In shear (or friction) experiments, the sample is moved tangentially to the sample surface (Fig. 5b).…”
Section: Force-displacement Curvesmentioning
confidence: 99%
“…[32,67,68,104,105] This necessitates either the calculation of the contact area from the displacement data or, even better, in situ visualization using a microscope. [31,33,61,63,[75][76][77][78] The change in contact area during the detachment phase is for structured surfaces even more complex, especially for relatively small probe diameters, as single fibrils or fibril clusters detach in a stepwise fashion, leading to non-circular contact areas. [33] To overcome the problems of changing contact area and inhomogeneous strain fields within the sample, adhesion experiments with flat probes were recently performed and compared to tests with spherical probes.…”
Section: Reviewmentioning
confidence: 99%
“…This fact has motivated many researchers to fabricate microfibril arrays 1-19 and to study their adhesion and friction behavior. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] It has been found that friction behavior of fibrillar arrays depends on the stiffness of the fibril material. For example, arrays made of soft fibrils with spatulated tips have static and dynamic friction that is lower than that of a flat control surface made of the same material.…”
Section: Introductionmentioning
confidence: 99%